COVID-19 in discharged patients with diabetes and chronic kidney disease: one-year follow-up and evaluation - Ran, Enrong; Zou, Yutong; Zhao, Chuanyi; Liu, Kai; Yuan, Jiamin; Yang, Wenjie; Zhao, Lijun; Yang, Qing; Yang, Jia; Ju, Xuegui; Cai, Linli; Lang, Yanlin; et al. (Frontiers in Endocrinology, 2025)
PurposeTo evaluate the all-cause mortality rate and renal outcomes in patients with diabetes and chronic kidney disease (CKD) following hospital discharge for COVID-19.MethodsThis single-center prospective observational study included 187 discharged COVID-19 patients with diabetes and CKD, admitted between December 2022 and January 2023 at West China Hospital, Sichuan University. Cox regression analysis was used to assess mortality risk, and logistic regression was applied to identify risk factors for rapid CKD progression after discharge.ResultsDuring the one-year follow-up, the all-cause mortality rate was 26.7%, with a COVID-19-related acute kidney injury (AKI) incidence of 35.3%, and 35.8% of patients experienced rapid CKD progression after discharge. Cox proportional hazards regression indicated that sepsis and mechanical ventilation were major risk factors for post-discharge all-cause mortality. Logistic regression identified baseline eGFR < 60 mL/min/1.73 m² as an independent risk factor for rapid CKD progression.ConclusionsDuring the one-year follow-up period, we observed that patients with diabetes and CKD exhibited higher all-cause mortality and experienced rapid deterioration of kidney function after acute infection with COVID-19. This underscores the importance of ongoing longitudinal follow-up to more accurately track the long-term health effects of COVID-19 on patients with diabetes and CKD.